1994
DOI: 10.1002/hlca.19940770813
|View full text |Cite
|
Sign up to set email alerts
|

Insertion Reactions of [ReH(CO)5–n(PMe3)n] Complexes (n = 2–4) with aldehydes, CO2, and activated acetylenes

Abstract: The complexes of the type [ReH(CO)5 -"(PMe,),,] (n = 2 , l ; n = 3, 2; n = 4,3) were reacted with aldehydes, C02, and RC=CCOOMe (R = H, Me) to establish a phosphine-substitutional effect on the reactivity of the Re-H bond. In the series 1-3, benzaldehyde showed conversion with only 3 to afford a (benzy1oxy)carbonyltetrakis(trimethy1phosphine)rhenium complex 4. Pyridine-2-carbaldehyde allowed reaction with all hydrides 1-3. With 1 and 2, the same dicarbonyl[(pyridin-2-yl)methoxy-O,N]bis(tnmethylphosphine)rheniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…42 Nietlispach et al synthesized a series of Re-hydride complexes ReH-(CO) n (PR 3 ) 5−n (n = 5, 4, 3, 2, 1 and R = Ph, CH 3 ) and showed that the hydridic character depends on the increasing number of phosphine ligand and they undergo insertion reactions with CO, CO 2 , CS 2 , and ketones. 43 Berke et al studied the unusual insertion behaviour in the metal-H bond of the chelated MoH-(dmpe) 2 NO complex (dmpe = 1,2-bis(dimethyl phosphino-)) with inactive imines 44 and argued that the high propensity of the dmpe ligand towards imine was due to the chelating effect of the cis-bidentate phosphine ligand which enhanced the hydridic character compared to MoH(NO)(CO) 2 (PR 3 ) 2 and MoH(NO)(CO)(PR 3 ) 3 . Abramov et al noted that substituting PPh 3 in place of the CO group in the system 1 gives higher hydridic character to the hydride ligand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Nietlispach et al synthesized a series of Re-hydride complexes ReH-(CO) n (PR 3 ) 5−n (n = 5, 4, 3, 2, 1 and R = Ph, CH 3 ) and showed that the hydridic character depends on the increasing number of phosphine ligand and they undergo insertion reactions with CO, CO 2 , CS 2 , and ketones. 43 Berke et al studied the unusual insertion behaviour in the metal-H bond of the chelated MoH-(dmpe) 2 NO complex (dmpe = 1,2-bis(dimethyl phosphino-)) with inactive imines 44 and argued that the high propensity of the dmpe ligand towards imine was due to the chelating effect of the cis-bidentate phosphine ligand which enhanced the hydridic character compared to MoH(NO)(CO) 2 (PR 3 ) 2 and MoH(NO)(CO)(PR 3 ) 3 . Abramov et al noted that substituting PPh 3 in place of the CO group in the system 1 gives higher hydridic character to the hydride ligand.…”
Section: Resultsmentioning
confidence: 99%
“…[39][40][41] Previously proton affinity, thermodynamic and various spectroscopic methods were used to characterize the electron donating character of a hydride ligand of metal hydride complexes. [42][43][44][45] In the present study a MESP based approach is presented to characterize the hydridic character of a hydride ligand in a metal complex, and the formation of electron rich hydride ligands in some metal hydride complexes is revealed for the facile liberation of dihydrogen from water.…”
Section: Introductionmentioning
confidence: 99%
“…There has been much interest in the reactions of metal hydride complexes with alkynes due to their relevance to catalysis and organometallic synthesis. In the case of rhenium, reactions of alkynes with several rhenium mono- and dihydride complexes have been reported: for example, ReH(CO) 5 , ReH(CO) 5− n (PMe 3 ) n ( n = 2−4), Cp 2 ReH, CpRe(CO)(NO)H, ReH(Rpz)(HRpz)(NO)(PPh 3 ) 2 , Re(Br)(H)(NO)(PR 3 ) 2 ] (R = Cy, i -Pr), [Re(η 2 -H 2 )(CO) 2 P 3 ] + (P = P(OEt) 3 , PPh(OEt) 2 , PPh 2 OEt), and [ReH 2 Cl(bpy)(PPh(OEt) 2 ) 3 ]BPh 4 . The reactions usually lead to insertion of alkynes into a Re−H bond to give η 1 -vinyl complexes, with the exception of [Re(η 2 -H 2 )(CO) 2 P 3 ] + , which reacts with terminal alkynes to give vinylidene complexes, and ReH(Rpz)(HRpz)(NO)(PPh 3 ) 2 , which reacts with arylacetylenes to give acetylide complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Reaction of 4 with CH 2 O (generated, in situ , by sonication of paraformaldehyde dispersed in acetone) occurs slowly in the dark and provides 3 as one of the products (the yield of 3 reaches a maximum of 25% after 1 h). This represents the first example of CH 2 O insertion into a rhenium hydride bond; however, Berke et al have shown that some rhenium−hydrides are capable of inserting aromatic aldehydes to give phenoxy derivatives. Under photolysis conditions, multiple products were generated from the reaction of 4 with CH 2 O in acetone and 3 was not present.…”
mentioning
confidence: 97%